Enhancing Place Identity Through Food Customization and Customer Delight: Evidence from Healthy Food Restaurants - Abdullah Abdulaziz Alhumud; Sally Mohamed Amer; Eman AbdelHameed Hasnin; Maha Ali Alsahely (Qubahan Academic Journal)
Nowadays, customization allows customers to become co-designers of a product by add- ing symbolic and emotional values to the product. Thus, customers' lives are shaped by the customiz- ing process and the decisions they must make. Despite, the extensive body of research on customiza- tion. The influence of food customization and customer delight on place identity has not received enough empirical investigation, this study aims to fill this gap. This study aims to evaluate how food customization influences customer delight and place identity. In addition, we examine the mediation role of customer delight in the relationship between food customization and place identity. Partial- least squares structural equation modelling (Warp-PLS V.7) and SPSS 26.0 were used to analyze the data collected from 432 customers of healthy food restaurants in Riyadh. The findings show that food customization has both direct and indirect effects on place identity, given that customer delight serves as a partial mediator. The study's findings offer insightful guidance that could help restaurant manag- ers do more to foster customers’ place identification by offering them customized services that strengthen their sense of customer delight.